Stiffness Characteristics of High-Speed Railway Turnout and the Effect on the Dynamic Train-Turnout Interaction - Jingmang Xu; Ping Wang; Xiaochuan Ma; Yuan Gao; Rong Chen (Shock and Vibration)
Track stiffness in railway turnouts is variable due to differences in structural composition along the longitudinal direction, which will lead to severe dynamic interaction between train and turnout. In this paper, a transient analysis model is presented to investigate the stiffness characteristics of high-speed railway turnouts based on the finite element method and is applied to optimise the stiffness of railway turnouts. Furthermore, the effect of the stiffness variations on the dynamic train-turnout interaction is analysed. The calculation results show that the track stiffness characteristics are similar in the main and diverging line of railway turnout, except for the check rail sections. Due to the existence of shared baseplates and spacer blocks between different rails, the stiffness variations in the crossing panel are most severe in high-speed railway turnouts. The stiffness differences (calculated as the ratio of the maximum and minimum stiffness) of the longitudinal and lateral direction for Chinese number 18 ballasted turnout are 216% and 229%, respectively. The graded stiffness of the tie pads has been redesigned to optimise the stiffness of railway turnout based on the transient analysis model and the stiffness differences of the turnout are decreased. Altogether, the dynamic train-turnout interaction is enhanced remarkably by considering the turnout’s stiffness characteristics.